Post-mortem stability of blubber retinoids in by-caught harbour porpoises (Phocoena phocoena): implications for the design of biomarker studies - Tornero, V.; Borrell, A.; Pubill , E.; Koopman, H.; Read, A.; Reijnders , P. J. H.; Aguilar, A. (J. Cetacean Res. Manage., 2023)
The effect of post-mortem time (0-48 hours) on retinoid concentrations in the blubber and liver of harbour porpoises under natural conditions is investigated to assess the stability of samples collected from animals after death. Organochlorine compounds and lipid content were also determined to assess their potential effects on retinoid status. Organochlorine concentrations remained low throughout the postmortem period and were considered unlikely to influence retinoid body dynamics. Retinoid concentrations in liver were 5-6 times higher than those in blubber and both were highly correlated. In contrast with liver, blubber can be easily sampled from live individuals using nondestructive biopsy techniques and is therefore considered an alternative tissue to assess retinoid status in marine mammals. Neither significant differences nor trends were detected in the concentration of retinoids over the studied period, indicating that degradation agents (ultraviolet rays, oxygen exposure and heat) did not affect them. Blubber can thus be regarded as a reliable tissue for the assessment of the retinoid status of unpreserved specimens kept up to 48 hours in conditions similar to those of this study.